Production of virus-free Kinnow mandarin and Mosambi sweet orange nucleus planting material through shoot tip grafting - and R.P. PANT, N.V. HOA, Y.S. AHLAWAT (Indian Phytopathology, 2004)
A protocol to develop virus-free nucleus planting material of Kinnow mandarin and Mosambi sweet orange through shoot-tip grafting (STG) was standardized. Among the rootstocks tested, Rough lemon was found more suitable for Kinnow but Mosambi grew better on its own root. Shoot tip grafts with apical meri stem having two leaf primordia were successful up to 20.83% and were free from viruses. The increase in size of scion increased the percentage of successful grafts. Shoot-tips pretreated with anti-oxidants and plant growth regulators increased the percentage of successful grafts as compared to control. Out of three methods of grafting applied for STG, triangular incision gave best result. We found that the in-vitro grafted plants when double grafted on rootstock in the glasshouse survived better than conventional hardening shoot tips with two leaf primordia were found free from Indian citrus ringspot virus (ICRSV), Citrus tristeza virus (CTV), Citrus Yellow Mosaic badnavirus (CYMBV), Citrus yellow vein clearing Virus (CYVCV).